Investigation of the Relationship between Informal Relations and Employee Creativity in Media Companies (International Journal of Applied Research in Management and Economics, 2018)
The present study investigates the relationship between the employees’ informal relations and their creativity. This research was conducted to recognize the informal relations of employees as one of the ways to enhance creativity in an organization. Data was gathered using the quantitative method and the questionnaire technique based on the human relations approach. Also, all employees of Media companies at Tehran were considered as the statistical population and 50 were examined as the samples of the study. After data analysis, the findings indicated that there was no relationship between creativity and informal relations, and informal relations cannot directly be considered to boost creativity.